Anthropometric and performance characteristics of young male soccer players competing in the UK - Russel, M.; Tooley, E. (Serbian Journal of Sports Sciences, 2011)
This study investigated the anthropometric and performance characteristics of 43 soccer players (age: 15 ± 2 years, height: 1.71 ± 0.08 m, mass: 63.9 ± 9.4 kg) who represented a UK-based Championship club in teams classified according to chronological age (i.e., under 14, under 16 or under 18 years of age). Anthropometrics and physical performances (countermovement jump; CMJ, 15 m and 30 m sprints, multistage fitness test) were measured. The under 18s age group were taller (p=0.007), heavier (p<0.001), jumped higher (p<0.001), sprinted faster (15 m sprint time: p=0.045; 30 m sprint time: p=0.011), and possessed a greater maximal aerobic capacity (p=0.003) than the under 14s players. However, players from the two youngest age groups were similar in all measurements (p>0.05). Additionally, high (64.6 ± 3.8 W•kg-1) or low (57.0 ± 2.8 W•kg-1) CMJ performances were able to differentiate between sprint times over 15 m (high, low: 2.38 ± 0.06 s, 2.44 ± 0.11 s; p=0.015) and 30 m (high, low: 4.18 ± 0.12 s, 4.32 ± 0.22 s; P=0.016). These results characterise the anthropometry and performance of UK-based soccer players of varying ages while highlighting the discriminative ability of certain tests to differentiate between sprint performances.